Mangiferin in combination with primaquine reduces disease progression and transmission potential while alleviating cerebral pathology through suppression of neural cell apoptosis in experimental cerebral malaria - Subham Halder; Saikat Mukherjee; Soubhik Ghosh; Poulomi Khamaru; Abhishek Choudhury; Pronabesh Ghosh; Altamas Hossain Daptary; Sayandeep Brahma; Atrayee Sengupta; Bidisha Chatterjee; Arindam Bhattacharyya (Inflammopharmacology, 2026)

Spermidine Attenuates Neuroimmune Dysfunction in Gulf War Illness via Modulation of the Gut- Brain Axis - Ayushi Trivedi; Subhajit Roy; Madhura More; Dipro Bose; Punnag Saha; Ram Kumar; Subham Sarkar; Jonathan Skupsky; Ashok Tuteja; Kimberly Sullivan; Nancy Klimas; Saurabh Chatterjee (Molecular Neurobiology, 2026)
Gulf War illness (GWI) affects nearly one-third of US veterans deployed during the 1990–1991 Gulf War (GW) and is characterized by chronic fatigue, neuroinflammation, and gut dysbiosis. Through comprehensive fecal metabolomics sequencing, our lab previously reported the depletion of beneficial metabolites including spermidine in the preclinical GWI mouse model. Spermidine is an endogenously synthesized polyamine known for its anti-inflammatory and mucosal barrier protective effects in various pathological diseases. Given its established role in mitigating intestinal inflammation and maintaining homeostasis, this study investigated the therapeutic potential of spermidine in a persistent (22 weeks) GWI mouse model, with a specific focus on gut–brain axis regulation. Our results demonstrated that spermidine effectively restored both microbial richness and diversity by selectively enriching beneficial bacterial taxa and suppressing growth of opportunistic pathogens, which are otherwise dysregulated following exposure to GW chemicals. Spermidine treatment also improved gut epithelial barrier integrity and reduced epithelial release of high-mobility group box 1 (HMGB1) into systemic circulation. Recent studies on GWI have implicated a critical role of gut-derived damage-associated molecular patterns (DAMPs), particularly HMGB1 in mediating neuroinflammation. Our findings indicate that systemic levels of HMGB1 critically influence the extent of blood–brain barrier (BBB) disruption and subsequent microglial activation. Mechanistically, spermidine activated intestinal aryl hydrocarbon receptor (AhR)/nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling, which played a role in limiting intestinal HMGB1 release and suppressing downstream receptor for advanced glycation end-product (RAGE)–mediated microglial activation in the brain. In vitro results indicate spermidine promoted AhR/Nrf2 nuclear translocation which reduced LPS-induced HMGB1 release from primary intestinal epithelial cells (IECs), effects abrogated by AhR inhibition. Additionally, we observed that HMGB1 directly induces microglial activation via RAGE receptors in immortalized microglial (IMG) cell lines in a dose-dependent manner. These results demonstrate that spermidine decreases neuroinflammation by modulating gut–brain axis pathophysiology associated with GWI. Together, this study demonstrates the therapeutic role of spermidine in ameliorating systemic and neurological disturbances in GWI. Graphical Abstract

Petrogenesis of magmatic charnockite-biotite granite suite from parts of the Chotanagpur Granite Gneissic Complex (CGGC), eastern Indian shield: Implication for the break down of the Columbia Supercontinent - Somdipta Chatterjee; Subham Mukherjee; Sanjoy Sanyal; Pulak Sengupta (Lithos, 2024)

Short-chain n-alkanes in benthic mats and mosses from the Larsemann Hills, East Antarctica - Subham Chatterjee; Supriyo Kumar Das; Pravat Kumar Behera; Devanita Ghosh; Arindam Chakraborty; Priyank Pravin Patel; Minoru Ikehara (Organic Geochemistry, 2023)